Greater gender diversity among autistic children by self-report and parent-report. (January 2023) - Corbett, Blythe A; Muscatello, Rachael A; Klemencic, Mark E; West, Millicent; Kim, Ahra; Strang, John F
Emerging research suggests overrepresentation of gender diversity among autistic youth. Previous gender diversity research with autistic children has relied on parent-report based on a single question. The Gender Diversity Screening Questionnaire–Self-Report and Parent-Report assessed gender diversity experiences from 244 children (140 autism spectrum disorder and 104 typically developing), between 10 and 13 years, and their parents. Parent-report Child Behavior Checklist Item-110, "Wishes to be the opposite sex, " was also collected. Autistic children endorsed higher Gender Diversity Screening Questionnaire–Self-Report Binary Gender Diversity, t (223.21) = –2.83, adjusted p  = 0.02, d  = –0.35, and Nonbinary Gender Diversity, t (191.15) = –3.79, adjusted p  = 0.001, d  = –0.46, than typically developing children. Similarly, for Gender Diversity Screening Questionnaire–Parent-Report, there was a significant gender-body incongruence difference between the groups, t (189.59) = –2.28, adjusted p  = 0.05, d  = –0.30. Within-group analyses revealed that parents of autistic females-assigned-at-birth reported significantly more gender-body incongruence than males-assigned-at-birth, t (32.91) = –3.78, p  < 0.001, d  = –1.11. Moreover, distinct within-group profiles of gender experiences and internalizing symptoms were revealed, showing associations between gender profiles and symptoms of anxiety, depression, and suicidality. Results extend reports showing increased rates of gender diversity in autistic children based on both self-report and parent-report, underscoring the need to better understand and support the unique and complex needs of autistic children who experience gender diversity. Lay abstract: Gender diversity broadly refers to the way in which an individual experiences (expressions and/or identities) their gender distinctly to that which would be expected based upon social norms for their gender assigned at birth. Recent research has shown a higher representation of gender diversity among autistic youth. Previous research in this area has relied on parent-report based on a single question from the Child Behavior Checklist Item-110, asking whether their child "Wishes to be the opposite sex." The Gender Diversity Screening Questionnaire Self-Report and Parent-Report were used to assess the experience of gender diversity in 244 children (140 autism spectrum disorder and 104 typically developing) between 10 and 13 years. The Item-110 was also collected. Results showed that autistic children endorsed much higher rates of Binary Gender Diversity (less identification with their designated sex and more with the other binary sex) and Nonbinary Gender Diversity (identification as neither male nor female) than typically developing children. Similarly, parents of autistic children reported significantly more gender-body incongruence experienced by their child than parents of typically developing children. Specifically, parents of autistic females-assigned-at-birth reported significantly more gender-body incongruence than autistic males-assigned-at-birth. Parent- and self-report measures were largely related. Moreover, statistical comparisons between and within the groups revealed associations between gender profiles and symptoms of anxiety, depression, and suicidality. Results extend previous reports showing increased rates of gender diversity in autistic children, now based on both self-report and parent-report, and highlight the need to better understand and support the unique and complex needs of autistic children who experience gender diversity.